Evolution mechanism of MgAlON in the Al-Al2O3–MgO composite at 1800 °C in flowing nitrogen. Issue 4 (March 2018) - Yan, Mingwei; Li, Yong; Li, Hongyu; Sun, Yang; Chen, Haiyang; Ma, Chenhong; Sun, Jialin
Abstract: The Al-Al2 O3 –MgO composite was calcined at 1800 ℃ in flowing nitrogen, using fused corundum, tabular alumina, activated α-Al2 O3, high purity magnesia and metal aluminum powder as raw materials and magnesium aluminate sol as binding agent. The calcined sample was characterized and analyzed by XRD, SEM and EDS, and evolution mechanism of MgAlON was studied. Formation mechanism of MgAlON can be described as follows. At elevated temperatures in flowing nitrogen, Al(g)/Al2 O(g) diffuses and transfers along pores or gaps in the Al-Al2 O3 –MgO composite, being nitrided as AlN, and then AlN reacts with Al2 O3 -rich spinel to form granular MgAlON. In gas-gas reaction system, Al(g)/Al2 O(g), N2 (g), Mg(g) and O2 (g) react to form flake MgAlON.